Socioeconomic determinants of the individual micro-entrepreneur (IME) - Morais, Mateus Cerqueira Anício; Emmendoerfer, Magnus Luiz; Vitória, José Ricardo; Mendes, Wesley de Almeida (REGEPE Entrepreneurship and Small Business Journal, 2022)
Objective: identifying the possible relationships between socioeconomic variables and the manifestation of the Individual Micro-Entrepreneur (IME). Methodology/approach: from the survey of characteristics of the IME, in databases in the Brazilian scope, under a quantitative approach, multiple regression analysis was applied, including social and economic variables of municipalities in Minas Gerais. Main results: there are significant effects of the variables education, income, and basic sanitation on the proportion of IME at the municipal level. Their values show that better socioeconomic conditions are inversely related to the IME. Theoretical/methodological contributions: this study contributes to the discussion on entrepreneurship policies and the types of businesses to be promoted by governments. It identifies its explanatory variables in developing countries. Relevance/originality: this study (a) strengthens the scientific construction based on the results of the institution of the legal framework of the IME in Brazil; and (b) it delves into issues related to the effect of socioeconomic variables on IME, covering entrepreneurship “for survival” and as a “lifestyle” – themes that are still little explored by the academic literature, especially when it involves developing countries. Social/management contributions: in practical terms, to present the social and economic realities of entrepreneurs benefiting from the IME legal apparatus provides grounds for reflecting and analyzing the expected effects of this public policy. JEL Code: L22, L26, L29, L38, O10, O20